An analysis of occupants response to thermal discomfort in green and conventional buildings in Malaysia - Azizi, Nurul Sakina Mokhtar; Wilkinson, Suzanne; Din, Moktar Aziz Mohd; Salim, Nuzaihan Aras Agus (Penerbit Akademia Baru, 2018)
The aim of this study is to examine what people do when they are too hot or too cold, and whether there are significant differences in the behaviour of occupants between green and conventional buildings. Case studies of green and conventional buildings were used in this study. Questionnaires were used as the tool to gain the relevant information from the building occupants of the case studies. Results showed that in response to feeling cold, three actions were significantly different between green and conventional buildings. One of the actions were on environmental adjustments (i.e. green building occupants were less likely to adjust the temperature system) and two were on personal adjustments (i.e. green building occupants less likely to put warmer clothes & less likely to alter timing of work pattern). While in response to feeling too hot, two actions were significantly different between the building types with one action from environmental adjustment (i.e. green building occupants less likely to adjust temperature system) and personal adjustment (i.e. green building occupants less likely to consume cold drinks/food). To date, there is limited understanding on whether green buildings have any different influences on how occupants behave in response to thermal discomfort. The findings in this study will aid designers to design better buildings that encourage better behaviour adaptations.